Health performance assessment modeling and its application to compact medical communities in China - Miao Yu; Zhongmou Huang; Dan Zhang; Yansui Yang; Ching‐Wen Chien; Hongwu Tuo (Wiley, 2024)
Abstract Some regions in China have already implemented capitation payment or capitation budget management for medical insurance funds. However, there remains a shortage of adequate tools and methodologies to accurately quantify differences in population health risks. Therefore, this paper constructs a health performance assessment model that comprises four steps. The first step is to categorize all participants into health risk groups based on whether they have contracted with a family doctor, their age, sex, and the type of consultation. The second step is to categorize health risk groups based on differences in healthcare resource utilization. The third step is to analyze health performance by examining healthcare resource utilization year over year. The fourth step is to apply the assessment results to assist local finance bureaus and medical insurance bureaus in developing incentive schemes. According to cost weights, the health risk groups are split into six classes: insured residents without health care visits, healthy insured person, slightly ill insured patients, ill insured patients, more seriously disease patients, and severely ill insured patients. We evaluate one compact medical community's health performance by examining changes in the proportion of resource usage group size and expense. From 2019 to 2021, both the proportion of patients with severe and ultra‐severe diseases and the proportion of costs in the sample increased, according to changes in resource utilization levels. This result indicates that the population's overall health has not improved and that the compact medical community is still primarily focused on treating diseases, with poor implementation of health maintenance measures and minimal improvement in health performance.